Market Structure of the Tofu Agroindustry - Rada, Adrianus; Nubatonis, Agustinus; PVMambru, Yohanis; Joka, Umbu (Agribusiness Journal, 2024)
Tofu is an easily accessible and cheap source of vegetable protein. The tofu industry in Kota Kefamenanu District is experiencing quite rapid development. This research aims to determine the market structure of the tofu industry in Kota Kefamenanu District. The sample was determined using a saturated sampling technique of 7 tofu industrial business units in the Kefamenanu City sub-district which includes villages (Tubuhue, Sasi, South Kefa, Maubeli and Central Kefa). The data analysis method used is a qualitative descriptive method, Market Structure (Market Share, Concentration Ratio, Herfindahl Hirschman Index). Based on the research results, the market structure of the tofu industry in Kota Kefamenanu sub-district is known to be controlled by a large market share with the highest level of market share control (MS) in UD. Sumber Hidup with a value of 23.9 % , while the lowest market share (MS) in the alpha omega industry has a value of 4.2%. Research on the concentration ratio of three companies (CR3) produces a tofu industry value of 60.6 % , so it can be seen that the value is 0.4â‰¤ CR3 0.8. Meanwhile, from the results of the Herfindahl Hirschman Index calculation, a value of 1735.4 % was obtained , meaning that the IHH value ranges between 1000-2500 or 0 IHH, so the tofu industrial market in Kota Kefamenanu District is in the Oligopoly market type..Â